Banxia Xiexin Decoction Ameliorates t-BHP-Induced Apoptosis in Pancreatic Beta Cells by Activating the PI3K/AKT/FOXO1 Signaling Pathway - Li-juan Du; Bing Pang; Yu-meng Tan; Ya-nan Yang; Mei-zhen Zhang; Qing Pang; Min Sun; Qing Ni (Journal of Diabetes Research)
Background. Banxia Xiexin Decoction (BXXD) reportedly regulates glycolipid metabolism and inhibits pancreatic β-cell apoptosis. This study is aimed at investigating the protective effect of BXXD on tert-butyl hydroperoxide- (t-BHP-) induced apoptosis in MIN6 cells and the underlying mechanisms. Methods. MIN6 cells were preincubated with BXXD or liraglutide (Li) with or without PI3K inhibitor LY294002 (LY) for 12 h, following which t-BHP was added to induce MIN6 cell apoptosis. The protective effects of BXXD on MIN6 cells were evaluated by detecting cell viability and proliferation and glucose-stimulated insulin secretion (GSIS). The antiapoptotic effects were evaluated by Hoechst 33342 staining and terminal deoxynucleotidyl transferase dUTP nick end labeling assay (TUNEL). Malondialdehyde and glutathione peroxidase content and superoxide dismutase activity were measured using commercial kits. The expression of PI3K/AKT/FOXO1 signaling pathway-related signal molecules, and that of apoptotic indicators Bax, P27, and Caspase-3, was quantified using western blotting. Results. Preincubation with BXXD significantly improved t-BHP-induced proliferation inhibition and apoptosis and enhanced GSIS. t-BHP induced the generation of reactive oxygen species and inhibited the activities of antioxidant enzymes, which could be neutralized by pretreatment with BXXD. BXXD promoted the phosphorylation of AKT and FOXO1 in t-BHP-induced MIN6 cells. Moreover, BXXD attenuated the expression of related apoptotic indicators Bax, P27, and Caspase-3. LY abolished these effects of BXXD. Conclusion. BXXD protected MIN6 cells against t-BHP-induced apoptosis and improved insulin secretory function through modulation of the PI3K/AKT pathway and the downstream FOXO1, thus suggesting a novel therapeutic approach for type 2 diabetes mellitus (T2DM).